Making distributed systems secure with program analysis and transformation. - Myers, Andrew
Building secure distributed systems is difficult, and making sure they are secure is even harder. For strong security, a variety of different mechanisms are used, such as encryption, digital signatures, access control, and replication. But once the system is built, it is difficult to know that system-level security objectives have been achieved.
Keywords: Software; Software engineering; Testing and debugging; Distributed debugging; Protection mechanisms; Information systems; Information storage and retrieval; Systems and software; Distributed systems; Computing milieux; Management of computing and information systems; Security and protection; Algorithms; Design; Theory